Multisensory Integration in the Mouse Striatum - Reig, Ramon (Cell Press, 2014)
The basal ganglia are involved in sensorimotor functions and action selection, both of which require the integration of sensory information. In order to determine how such sensory inputs are integrated, we obtained whole-cell recordings in mouse dorsal striatum during presentation of tactile and visual stimuli. All recorded neurons responded to bilateral whisker stimulation, and a subpopulation also responded to visual stimulation. Neurons responding to both visual and tactile stimuli were located in dorsomedial striatum, whereas those responding only to whisker deflections were located dorsolaterally. Responses were mediated by overlapping excitation and inhibition, with excitation onset preceding that of inhibition by several milliseconds. Responses differed according to the type of neuron, with direct pathway MSNs having larger responses and longer latencies between ipsilateral and contralateral responses than indirect pathway MSNs. Our results suggest that striatum acts as a sensory “hub” with specialized functional roles for the different neuron types.